2015
DOI: 10.4209/aaqr.2014.07.0143
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification of Aerosol Sources and Types as Measured over Jaipur, India

Abstract: The aerosol properties retrieved from the AErosol RObotic NETwork (AERONET) measurements during the period 2009 to 2012 over Jaipur (26.9°N, 75.8°E, 450m asl) in Northwestern India are used for the first time to identify the types of aerosols. In order to consider the appropriate threshold of aerosol optical thickness (τ) at 500 nm (τ 500 ) and Angstrom exponent (α) in the spectral band 440-870 nm, a novel approach has been conducted and applied for the identification process. Five prevailing aerosol classes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 38 publications
1
49
0
1
Order By: Relevance
“…However, it can explain the fact that less measurements are available during the wet season for Abidjan than Cotonou because of cloud cover. The W season shows the lowest Ångström exponent value and low AOD, which reflects the contribution of maritime aerosols (Kaskaoutis et al, 2009;Verma et al, 2015;Toledano et al, 2007). Figure 7 shows that during the largest peak values (above 100 µg m −3 ) in the dry season, D1 and D2 are associated with an Ångström exponent close to 0.5, which means that advected dust might sporadically contribute to the increase in the ground-level PM 2.5 concentration.…”
Section: Aodmentioning
confidence: 93%
See 2 more Smart Citations
“…However, it can explain the fact that less measurements are available during the wet season for Abidjan than Cotonou because of cloud cover. The W season shows the lowest Ångström exponent value and low AOD, which reflects the contribution of maritime aerosols (Kaskaoutis et al, 2009;Verma et al, 2015;Toledano et al, 2007). Figure 7 shows that during the largest peak values (above 100 µg m −3 ) in the dry season, D1 and D2 are associated with an Ångström exponent close to 0.5, which means that advected dust might sporadically contribute to the increase in the ground-level PM 2.5 concentration.…”
Section: Aodmentioning
confidence: 93%
“…Following Kaufman et al (2000), large particles (dust or maritime aerosols) are dominant in the size distribution when the Ångström coefficient is below 0.7, although Toledano et al (2007) have reported a threshold of 1.05. A low value, typically below 0.8, of the Ångström exponent associated with high AOD, typically above 0.6 (Verma et al, 2015), indicates a significant contribution of coarse dust-like particles to the AOD (Balarabe et al, 2016).…”
Section: Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…The two locations, Ahmedabad and Jaipur in the western expanse of IGP exhibit differences in terms of aerosol type and the values. AODs are higher over Jaipur (Verma et al, 2015) when compared to Ahmedabad . The arid background aerosols are predominant over Jaipur, .…”
Section: Study Locations and Regionsmentioning
confidence: 80%
“…The arid background aerosols are predominant over Jaipur, . Single scattering albedo was found to be higher over Jaipur indicating that the aerosols over Jaipur are more scattering in nature (Verma et al, 2015), while the aerosols are more absorbing in nature over Ahmedabad . Similarly, the locations in the north/northeastern IGP, namely, Kanpur and Gandhi College show prominent spatial variations in terms of aerosol characteristics, sources and types (Kedia et al, 2014).…”
Section: Study Locations and Regionsmentioning
confidence: 98%